Detection of Staphylococcus aureus and antibiotic sensitivity pattern in mastitic cases from Namakkal District - Navaneetha, R; Saravanan, S (Indian Journal of Dairy Science, 2021)
Milk samples (n= 241) were collected from clinical and subclinical mastitic cows which were brought to teaching veterinary clinical complex (TVCC), Veterinary College and Research Institute (VC&RI), Namakkal, Tamil Nadu and subjected to isolation on mannitol salt agar, Gram’s staining and confirmation by polymerase chain reaction (PCR) using specific primers. The prevalence of Staphylococcus aureus at cow level was 61.5 and 57.4 per cent in clinical and subclinical cases, respectively, and at quarter level was 58.8 and 57.4 per cent in the clinical and subclinical cases, respectively. Antibiotic sensitivity pattern revealed a high sensitivity to enrofloxacin (100.0%) and a high resistance to methicillin (100.0%) by S. aureus isolates, and multidrug resistance by S. aureus isolates was also observed.